Sensitive and Reliable Indicator between Broca’s Index and Metropolitan Life Insurance Height - Weight Charts in First Year Medical Student - D. Godia, Dr. Haresh; Nikam, Dr. Lalit H (International Journal of Innovative Research in Medical Science, 2018)
Aims: This study was confined to healthy groups. Care was taken to exclude persons suffering from obvious disease and/ or recent history of illness Aims and Objective of present study are:- To assess out a sensitive and reliable indicator between Broca’s Index and Metropolitan Life Insurance Height - Weight charts. Materials and Methods: The present study were carried out on 100 1st M.B.B.S. students of GSMC Mumbai and Tertiary Care Hospital Mumbai (50 males and 50 females) not suffering from any major illness. Conclusion: Broca’s Index does not take build into consideration. It therefore gives high values for weight. On the other hand Metropolitan Life Insurance Tables give more accurate estimate of person’s nutritional status and they should be used as a reliable indicator for nutritional assessment. Adolescence, being an important period of physiological and psychological changes occurring in the body; is important since these changes can have effect in diet and nutrition of an individual leading to improper consumption of food and various deficiency diseases. Studies carried out on adolescents are very limited and it is needed to assess the nutritional status of adolescents